Contextual factors influencing decision making: Perceptions of professional soccer players - Levi, H. R.; Jackson, R. C. (Psychology of Sport and Exercise, 2018)
Objectives: This study sought to explore highly-skilled soccer players` perceptions of how contextual factors influence their decision making during matches. Design: A qualitative design was used in which individual semi-structured interviews were conducted with eight professional male soccer players aged between 18 and 22 years. Method: An interview schedule was designed to explore the perceived influence of a range of situational factors on decision making during matches. The interviews were recorded and transcribed verbatim. The data were analysed via an inductive thematic analysis. Results: Seven themes were identified from the data. The four dynamic contextual themes were: (a) personal performance, (b) score status, (c) momentum, and (d) external/coach instructions. The three static contextual themes were: (a) match importance, (b) personal pressures, and (c) preparation. Conclusions: The results highlight the importance of considering the dynamic and static context within which highly-skilled soccer players make decisions.